Pathological response in the breast and axillary lymph nodes after neoadjuvant systemic treatment in patients with initially node-positive breast cancer correlates with disease free survival: an exploratory analysis of the GeparOcto trial - Gerber, Bernd; Schneeweiss, Andreas; Möbus, Volker; Golatta, Michael; Tesch, Hans; Krug, David; Hanusch, Claus Alexander; Denkert, Carsten; Lübbe, Kristina; Heil, Jörg; Huober, Jens; Ataseven, Beyhan; et al. (Cancers, 2022)
Background: The conversion of initially histologically confirmed axillary lymph node-positive (pN+) to ypN0 after neoadjuvant systemic treatment (NAST) is an important prognostic factor in breast cancer (BC) patients and may influence surgical de-escalation strategies. We aimed to determine pCR rates in lymph nodes (pCR-LN), the breast (pCR-B), and both (tpCR) in women who present with pN+ BC, to assess predictors for response and the impact of pCR-LN, pCR-B, and tpCR on invasive disease-free survival (iDFS). Methods: Retrospective, exploratory analysis of 242 patients with pN+ at diagnosis from the multicentric, randomized GeparOcto trial. Results: Of 242 patients with initially pN+ disease, 134 (55.4%) had a pCR-LN, and 109 (45.0%) a pCR-B. Of the 109 pCR-B patients, 9 (8.3%) patients had involved LN, and 100 (41.3%) patients had tpCR. Those with involved LN still had a bad prognosis. As expected, pCR-B and intrinsic subtypes (TNBC and HER2+) were identified as independent predictors of pCR-LN. pCR-LN (ypN0; hazard ratio 0.42; 95%, CI 0.23-0.75; p = 0.0028 for iDFS) was the strongest independent prognostic factor. Conclusions: In initially pN+ patients undergoing NAST, the conversion to ypN0 is of high prognostic value. Surgical axillary staging after NAST is still essential in these patients to offer tailored treatment.